Breeding dominant genic male sterility restorer line of Brassica napus L. - Junying Zhang (Oil Crop Science, 2020)
To facilate breeding process of Brassica napus, a microspore culture and molecular marker-assisted screening combined system were proposed in this research. At early flowering stage, F1 offspring of hybridized combination HY15A ​× ​HF06 was used as donor for microspore culture to analyze effects of colchicine concentration on embryogenic and diploid rates of microspore. Treatment with 50 ​mg/L colchicine resulted in embryogenic rate of 3.56 embryos/bud, which was substantially higher than control (0.78 embryos/bud). A total of 1,387 embryos and 862 single plants were obtained after induction culture. Ploidy detection was performed for the regenerated plants by flow cytometry. Diploid rates of microspores treated with 50 ​mg/L and 70 ​mg/L colchicine were 17.2% and 21.0% respectively, which was significantly higher than control (10.5%). Totally 108 single plants that doubled successfully were randomly selected and screened using molecular marker BE10. Approximately 54 of 108 plants generated a 305 bp amplification product, whereas the other 54 plants showed a 398 bp band, thereby satisfying 1:1 separation ratio (x20.05 ​= ​0.0093). These coincided with field identification results. Findings of this study indicated that homozygous breeding material could be obtained by microspore culture in a short time, thereby remarkably accelerate breeding.